2021
DOI: 10.1177/23259671211033882
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Plain Radiographs Versus Magnetic Resonance Imaging to Measure Tibial Slope in Sports Medicine Patients: Can They Be Used Interchangeably?

Abstract: Background: The slope of the tibial plateau has been proposed as a reason for failure of anterior cruciate ligament reconstruction. Purpose: To evaluate the interobserver reliability of measurements of tibial slope on radiographs versus magnetic resonance imaging (MRI) scans and to assess whether the modalities can be used interchangeably for this purpose. Study Design: Cohort study (diagnosis); Level of evidence, 3. Methods: This retrospective study included 81 patients aged 18 to 30 years who were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
(86 reference statements)
1
12
0
Order By: Relevance
“…The variability in tibial slope measurements among different methods and imaging modalities has been investigated by several studies. 15,19,23,29 Naendrup et al 29 found that PTS measurements have a high degree of variability between measurement methods and imaging modalities, reporting a difference of up to 5° between methods. Jahn et al 23 recently found that the MPTS was larger by approximately 5° on radiography compared with MRI, with the LPTS being 2° greater on radiography.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variability in tibial slope measurements among different methods and imaging modalities has been investigated by several studies. 15,19,23,29 Naendrup et al 29 found that PTS measurements have a high degree of variability between measurement methods and imaging modalities, reporting a difference of up to 5° between methods. Jahn et al 23 recently found that the MPTS was larger by approximately 5° on radiography compared with MRI, with the LPTS being 2° greater on radiography.…”
Section: Discussionmentioning
confidence: 99%
“…13,30,38 Furthermore, these comparisons have been limited to either lateral radiography or magnetic resonance imaging (MRI), 13,17,30,38 although it has been shown that PTS values derived from radiography versus MRI may differ by up to 5°. 23…”
mentioning
confidence: 99%
“…The primary limitation of this study is that only conventional MRI was used to measure the morphological parameters of this study, instead of 3D-MRI examination. When morphological parameters are measured, the ideal sagittal section should be perpendicular to the line connecting the posterior condyle of the femur [ 25 ], which is difficult to ensure with conventional MRI [ 26 ]. Conventional MRI with excessive section thickness will make it difficult to accurately identify the sections and points of interest, resulting in errors [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The difference was 0.4° for each TSK and TSH. Jahn et al retrospectively examined images of 81 patients to compare measurements of medial and lateral TS between radiographs and MRI [ 42 ]. The authors pointed out that in an exactly lateral radiograph, the medial and lateral TS can obtain reproducible measurements.…”
Section: Discussionmentioning
confidence: 99%